2017
DOI: 10.1177/1938640016685147
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Hallux Valgus Surgery Without Distal Metatarsal Articular Angle Correction

Abstract: Level II: Prospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Three of the analyzed Reverdin-Isham studies reported a total correction of 3˚ for IMA (30)(31)(32), while the other three studies even less than 3˚ (31,36,42). Insufficient radiographic correction following the MIS Reverdin-Isham osteotomy has been already described (47). Nevertheless, this procedure was meant to be a valid procedure for correcting a hallux valgus deformity and is still a frequently used minimally invasive technique for hallux valgus correction (47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three of the analyzed Reverdin-Isham studies reported a total correction of 3˚ for IMA (30)(31)(32), while the other three studies even less than 3˚ (31,36,42). Insufficient radiographic correction following the MIS Reverdin-Isham osteotomy has been already described (47). Nevertheless, this procedure was meant to be a valid procedure for correcting a hallux valgus deformity and is still a frequently used minimally invasive technique for hallux valgus correction (47).…”
Section: Discussionmentioning
confidence: 99%
“…Insufficient radiographic correction following the MIS Reverdin-Isham osteotomy has been already described (47). Nevertheless, this procedure was meant to be a valid procedure for correcting a hallux valgus deformity and is still a frequently used minimally invasive technique for hallux valgus correction (47).…”
Section: Discussionmentioning
confidence: 99%
“…Scarf osteotomy is a technically challenging procedure with a potential ability to provide 3-plane correction of the hallux valgus deformity. 5 Scarf osteotomy allows for shortening or lengthening, rotation, horizontal displacement, depression, or elevation of the first metatarsal head. 4 The main correction of the deformity is achieved by lateral translation of the distal fragment, which allows for substantial reduction of IMA.…”
Section: Discussionmentioning
confidence: 99%
“…Uncorrected distal metatarsal articular angle (DMAA) is one of the risk factors for recurrence of the deformity. 4,5,10,11,21 If necessary, a shorter osteotomy with a greater rotational effect is created, to ensure proximal translation and correction of the DMAA and to avoid impingement with the second metatarsal. 6,15 Once impaction is achieved, the excessive medial overhanging cortical-cancellous triangular bony fragment is resected, preserved, turned upside down, and impacted into the proximal plantar medullary canal.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, which structures must be detached remains unclear. 5 , 10 , 26 , 36 These data, among other reasons, may explain the persistent high overall recurrence rate of HV deformity (2.7% to 73%). 2 , 4 , 9 , 31 , 33 …”
Section: Introductionmentioning
confidence: 99%